Sex, pornography and medicines in the markets of Dhaka - Rashid, Sabina F; Anam, Mujibul; Akram, O (© 2012 Taylor and Francis, 2017)
This book chapter was published in the Technologies of Sexuality, Identity and Sexual Health [© 2012 Taylor and Francis] and the definite version is available at: http://www.tandfebooks.com/isbn/9780203121689